Management of Facilities and Infrastructure of Physical Education in State Junior High School - Jajang, Jajang; Purwanto, Sugeng; Nanda, Fitri Agung; Novriansyah, Novriansyah (LPPM Undiksha, 2021)
Management of infrastructure and facilities is important in physical education, considering that infrastructure is a medium to support the success of learning. This study aims to determine how the management of physical education facilities and infrastructure in State Junior High Schools. This research is a type of qualitative research using a case study research design. Data obtained through interviews, observation, and documentation. The research data were obtained from six sources consisting of the principal, physical education teachers, and facilities and infrastructure staff. Data analysis used Miles and Huberman analysis. The results of research on the availability and management of facilities and infrastructure revealed that there were several physical education facilities and infrastructure that were feasible but had their availability. The removal of physical education facilities and infrastructure activities that have not been carried out properly has resulted in many damaged facilities and infrastructure piled up in the warehouse. The inventory process has been carried out well. This can be seen from the process of registering goods or facilities and infrastructure which are recorded alphabetically by the names of items that have been spent, the inventory process is carried out routinely and regularly. The process of maintaining physical education facilities and infrastructure is carried out by teachers and students.